Peran Relasi Pada Pemilu 2019 Di Kota Padangsidimpuan - Reunisah Darwanti Putri Siregar; Syafri Gunawan; Ahmatnijar Ahmatnijar (IAIN Padangsidimpuan, 2021)
This research is entitled The Role of Democratic Volunteers in Increasing Voter Participation in the 2019 General Election in Padangsidimpuan City. This study aims to determine the role of Padangsidimpuan Democracy Volunteers in increasing voter participation in the 2019 General Election in Padangsidimpuan City, as well as the obstacles experienced by Padangsidimpuan Democracy Volunteers in increasing voter participation in the 2019 General Election in Padangsidimpuan City. Descriptive qualitative research is the research method used in this study. This type of research uses field research, namely research that goes directly to the location that is the object of research or field research, and this research prioritizes a problem that is being studied and obtains more information in the form of words or sentences compared to information in the form of numbers. The results of this study indicate that the role of Padangsidimpuan Democracy Volunteers in increasing voter participation in the 2019 General Election in Padangsidimpuan City is to conduct direct socialization to the people of Padangsidimpuan City, where in conducting socialization of Democracy Volunteers are divided based on 10 bases. Voter and Election Education to the public in the form of, among others; Face to face, group discussions, simulations, lectures, posting socialization materials to social media. And the inhibiting factors for Padangsidimpuan Democracy Volunteers in increasing voter participation in the 2019 General Election in Padangsidimpuan City are obstacles that come from internal Democratic Volunteers, namely there are still many Democratic Volunteers members who are not confident in conveying socialization materials, the background of members of the Democracy Volunteers, No the structure of programs run by Democratic Volunteers, and the short tenure of Democracy Volunteers. And also obstacles that come from external factors, namely, the community's confidence is still lacking in the election, the difficulty of gathering the community to conduct election socialization, the difficulty of communication from the Democratic Volunteers to people with disabilities and also technical obstacles in voting such as registering A5, not having an ID card and assistance when choose.